TINJAUAN YURIDIS KEDUDUKAN HUKUM TANAH TIMBUL (STUDI DI KECAMATAN DEWANTARA KABUPATEN ACEH UTARA) - Azzahra, Nabila; Yamin, Muhammad; Zaidar, Zaidar (BULETIN KONSTITUSI, 2023)
ABSTRACT            A natural event resulting in the formation of new land which known as a land rising has the potential to be a place to live or a source of income. One of the cases is the land rising is at Bangka Jaya Sub-district, Aceh Utara Regency. The Law No. 11/2020 concerning on Job Creation is expected to be the most recent reference in overcoming various problem, one of which is Indonesian agrarian sector. However, there has been no detailed regulation on the rising land in many regions of Indonesia. Therefore, the issues addressed in this study are the Indonesian law/regulation following the enactment of Law No. Il of 2020 on Job Creation, the legal protection of the land rising possession at Bangka Jaya beach, Dewantara Sub-district, Aceh Utara Regency, as well as the process of submitting land rising ownership right at Bangka Jaya beach, Dewantara Sub-district, Aceh Utara Regency.            This empirical juridical research with qualitative and analytical descriptive study is employed. The primary and secondary data are collected through documents, observation, and in-depth interview.            The findings indicate that the regulation of land rising is not detailed in Law No. 11 of 2020 concerning Job Creation. However, according to government regulation No. 18 of 2021 on Management Rights, Land Rights, Flats Units, and Land Registration, land rights are state property. There is no legal protection for the community who occupy the land rising which is similar to the occupation of the land rising occurred in other places. As a result ofthe absence of legal certainty, the submission process of land ownership in Bangka Jaya beach can not be carried out. It is expected that the government create a special regulation such as Qanun concerning the land rising due to the potential cases of land rising in Aceh and other cities. A legal advice/socialization on illegal land ownership and the consequences, so the local government starts mapping on the land rising around Bangka Jaya coastal area.